Cholelithiasis with epigastric hernia in down’s syndrome: a case report - Kankaria, Jeevan; Madagond, Santosh (International Surgery Journal, 2022)
Down’s syndrome is associated with various congenital anomalies, musculoskeletal abnormalities and also various anatomical variation in organ systems. In this report we are presenting a case of cholelithiasis with Epigastric hernia in 42 years Male down’s syndrome patient, on laparoscopic exploration found multiple rectus sheath defects in epigastric region and Moynihan hump. A rare case of Down’s syndrome with multiple anterior abdominal wall defects.